Effects of temperature on the performance of anaerobic co-digestion of vegetable waste and swine manure - Ren, Haiwei; Mei, Zili; Fan, Wenguang; Wang, Yujie; Liu, Feifei; Luo, Tao; Li, Dong; Li, Zhizhong; Feng, Rong (International Journal of Agricultural and Biological Engineering, 2018)
The amount of vegetable wastes (VW) obtained from vegetable supply chain increased rapidly in recent years in China, which has posed environmental pollution problems. In view of the high moisture and organic content of VW, anaerobic digestion (AD) has shown to be an alternative with multi-environmental benefits such as waste disposal and renewable energy production. In this research, the anaerobic co-digestion of VW and swine manure (SM) in a 10 L fed-batch anaerobic digester was investigated, and the effects of temperature at psychrophilic (20°C), mesophilic (32°C and 37°C) and thermophilic (55°C) conditions on biogas production characteristics were studied with the aim of finding the better temperature for the enhanced performance of co-digestion. The results indicated that the operation performance of the anaerobic digester were maintained stability with no accumulation of volatile fatty acids (VFA) at mesophilic and thermophilic condition, as indicated by the low VFA/alkalinity ratio, which was lower than 0.10. The results of anaerobic co-digestion also showed that the value of pH, ammonia nitrogen (NH4+-N) and VFA ranked in normal range. The optimal temperature for co-digestion of VW with SM was mesophilic digestion at 32°C. Under this condition, the biogas and methane production yields reached 463.16 L/kg VS and 256.24 L CH4/kg VS, respectively. The average methane content in biogas at 32°C was the highest and reached 55.33%. Anaerobic digestion at 37°C and 55°C provided slightly lower methane yields of 93.75 L CH4/kg VS and 143.16 L CH4/kg VS, respectively. The lowest methane yield of 22.17 L CH4/kg VS was obtained at 20°C, with 22.88% of methane composition in biogas. The pilot-scale experimental results in 3 m3 household biogas digester showed that the cumulative biogas production was 70.52 m3 during the 42 d fermentation period. The average daily biogas production was 1.680 m3 and the average content of CH4 was 58.2%. The experimental results showed that the co-digestion with VW and SM at 32°C in a household biogas system could improve the stability of anaerobic process and achieve a higher biogas yield, which can satisfy farmers’ domestic biogas demand. Keywords: vegetable wastes, swine manure, anaerobic co-digestion, temperature, household biogas digester DOI: 10.25165/j.ijabe.20181101.3706 Citation: Ren H W, Mei Z L, Fan W G, Wang Y J, Liu F F, Luo T, et al. Effects of temperature on the performance of anaerobic co-digestion of vegetable waste and swine manure. Int J Agric & Biol Eng, 2018; 11(1): 218–225.